Serving truth with development news - Julius Chan (Asia Pacific Network, 1995)
Flawed journalism has sullied Papua New Guinea's good name and built up an unfortunate but valid distrust of the media. The country and its problems have been the victim of shallow journalists unable to look past the bad.